Sukarno’s Persona: Building Supremacy through Political Shibboleths - Maiddin, Sahul Hamid Mohamed; Ariffin, Khairi; Ramle, Muhammad Rozaimi (International Journal of Psychosocial Rehabilitation, 2020)
Sukarno, the first President of Indonesia, introduced a new political approach known as the Guided Democracy (GD) in August 1959. Along with its inception, he coined and disseminated some of the most venerated and remembered concepts in Indonesian political history such as Pancasila, Manipol-USDEK, NASAKOM and Marhaenism ideology. Sukarno’s personality was a central attention during the GD. The glorification led to his supremacy, thus provided him an opportunity to dominate his people with the creation of political shibboleths. This paper discusses his sloganeering efforts with assistance from government propaganda bodies as well as his political proponents. It begins with a concise introduction of his biography to demonstrate that the effort to instill the cult of personality has begun ever since his childhood days. This paper then examines the emergence and development of Sukarno’s revolutionary and political slogans like Revolusi (the Revolution) and Pancasila, which are amongst the most popular and powerful concepts employed by Sukarno to engage the public. The aim of this study is to show that Sukarno’s persona itself was a crucial factor in moving and building the Indonesian nation since its independence in 1945. This study is carried out using qualitative analysis methods, by employing primary and secondary sources such as newspapers, official publications, magazines and books. This paper suggests that as a central figure from 1959 to 1965, Sukarno successfully influenced and manipulated the Indonesian political ambience through the expert use of propaganda and rhetorical speech.